The relationship between population and economic growth in Malaysia / Jesse John Sian - John Sian, Jesse (2010)
The number of Malaysia's population is increasing year by year. Besides, population has played an important role not only in stimulating the economic growth in Malaysia but also contributed significantly to the growth of certain sectors especially in the industrial and manufacturing sector that demand high labour. Apart from that, a large population also provides a large domestic market for the economy. Moreover, population growth encourages competition, which induced technological advancements and innovations. The primary aim of this research is to identify the relationship between population and economic growth in Malaysia and this is done through reviewing the existing literature. Besides, the data is taken generally from the year 1980-2009. This study employs the Ordinary Least Square (OLS) method in order to examine the relationship between the population and economic growth. The result of the ordinary least square (OLS) shows that the finding in this study strongly support the null hypothesis that there is a positive relationship between population and economic growth. Besides that, the result from the finding is consistent with Bilal Savas, who the evidence of a long-run relationship between population and real per capita income and provides strongs support for the hypothesis that population is driving growth. Overall, the relationship between population and economic growth is strong and positive in the CAEs over the period of the analysis.